Diastolic dysfunction in Behçet's disease and its relationship with clinical manifestations of the disease: A case-control study - Gizem Varkal,; Rabia Eker Akıllı,; İpek Türk,; Zeynep Tüzün,; Burak Mete,; Süleyman Özbek, (Archives of Rheumatology, 2024)
Objectives: The study aimed to evaluate the frequency of diastolic dysfunction (DD) in patients with Behçet's disease (BD) and its relationship with clinical manifestations. Patients and methods: Seventy patients (35 females, 35 males; mean age: 39.3±11.0 years; range, 21 to 61 years) with BD and 50 healthy controls (27 females, 23 males; mean age: 38.8±10.0 years; range, 23 to 62 years) were included in the case-control study between October 2023 and December 2023. Age, sex, smoking status, disease duration, mucocutaneous involvement, other organ involvement, treatment received of the patients were recorded. The E/A ratio (the ratio of early diastolic wave to the atrial wave) and the E/E' ratio (the ratio of early transmitral filling velocity to early diastolic mitral annular velocity), which are markers of DD, were measured by transthoracic echocardiography. Results: Diastolic dysfunction was observed in 27.1% (n=19) of BD patients and 8% (n=4) of healthy controls (p=0.017). Male dominance was observed in patients with major organ involvement (MOI) compared to patients with isolated mucocutaneous involvement (p=0.001). While MOI was observed at a rate of 65.7%, ocular involvement, among the MOIs, constituted 52.9% of all BD patients. The percentage of patients with a mitral E/A ratio <1 was similar between the MOI and isolated mucocutaneous involvement groups. However, vascular involvement was observed in 47.4% of BD patients with a mitral E/A ratio <1 (p=0.034). In addition, it was observed that the group with a mitral E/A ratio <1 was older, had a longer disease duration, and had a higher erythrocyte sedimentation rate. Conclusion: Diastolic dysfunction is an early sign of cardiac involvement, and prolonged vascular involvement in BD increases the risk of DD.